A fine-tuned defense at the pea root caps: Involvement of border cells and arabinogalactan proteins against soilborne diseases - Fortier, Mélanie; Lemaitre, Vincent; Gaudry, Alexia; Pawlak, Barbara; Driouich, Azeddine; Follet-Gueye, Marie-Laure; Vicré, Maïté (Frontiers in Plant Science, 2023)
Plants have to cope with a myriad of soilborne pathogens that aﬀect crop production and food security. The complex interactions between the root system and microorganisms are determinant for the whole plant health. However, the knowledge regarding root defense responses is limited as compared to the aerial parts of the plant. Immune responses in roots appear to be tissue-speciﬁc suggesting a compartmentalization of defense mechanisms in these organs. The root cap releases cells termed root “associated cap-derived cells” (AC-DCs) or “border cells” embedded in a thick mucilage layer forming the root extracellular trap (RET) dedicated to root protection against soil-borne pathogens. Pea (Pisum sativum) is the plant model used to characterize the composition of the RET and to unravel its function in root defense. The objective of this paper is to review modes of action of the RET from pea against diverse pathogens with a special focus on root rot disease caused by Aphanomyces euteiches, one of the most widely occurring and large-scale pea crop diseases. The RET, at the interface between the soil and the root, is enriched in antimicrobial compounds including defense-related proteins, secondary metabolites, and glycan-containing molecules. More especially arabinogalactan proteins (AGPs), a family of plant extracellular proteoglycans belonging to the hydroxyproline-rich glycoproteins were found to be particularly present in pea border cells and mucilage. Herein, we discuss the role of RET and AGPs in the interaction between roots and microorganisms and future potential developments for pea crop protection.